PENGARUH ISLAM TERHADAP PEMBENTUKAN IDENTITAS BUDAYA MASYARAKAT MELAYU - Arief Maulana (Yayasan An-Nur Meunara Baro, 2025)
This article explores the influence of Islam in shaping the cultural identity of the Malay community a historical process that unfolded through trade routes, Islamic preaching (da'wah), and educational institutions since the 13th century CE. Islamization in the Malay world was not merely the spread of a religion but a complex cultural transformation that resulted in a synthesis between Islamic teachings and local traditions. This study aims to identify and analyze the changes in belief systems, the transformation of social values, and the manifestation of the Malay-Islamic identity in contemporary life. The research adopts a cultural anthropology and historical approach, with data collected through literature studies and cultural observation. The findings indicate that the arrival of Islam gradually replaced the animistic and Hindu-Buddhist belief structures with a monotheistic worldview based on tawhid (the oneness of God). Islam also influenced various cultural expressions, including oral traditions, literature, and social practices. Rather than erasing local elements, Islam integrated and transformed them through a selective process, resulting in a unique and rooted Malay-Islamic identity. This identity functions not only as a religious marker but also plays a vital role in shaping the direction of cultural, educational, and political policies in the Malay world today. The study also highlights the urgency of preserving the Malay-Islamic identity amid globalization and offers recommendations for further interdisciplinary research on the topic.